Establishing democracies - Fischer, Mary Ellen (Boulder, CO : Westview Press, 1996)
Balancing historical and contemporary cases, this comparative text examines the crucial question of what promotes or prevents the successful founding of democratic systems. Underscoring lessons learned from successful regime change and assessing current efforts to establish democracies whose ultimate fate is yet uncertain, this book will enable students to evaluate the chances of success for societies making the transition from an authoritarian or communist regime. The case studies are placed in context by a substantial introduction surveying theories of democracy and democratic transition and a conclusion comparing the cases and suggesting common patterns in the establishment of successful democracies. Created for upper-level students, this book can be used as a primary text to be supplemented by theoretical readings or as a source of additional case studies. Extensive notes provide a wealth of suggestions for further reading and research.
Introduction / Mary Ellen Fischer -- 1. England: An Unfinished Revolution / Patricia-Ann Lee -- 2. The United States: Creating the Republic / Tadahisa Kuroda and Erwin L. Levine -- 3. Germany: Into the Stream of Democracy / Roy H. Ginsberg -- 4. Japan: Foreign Occupation and Democratic Transition / Steven A. Hoffmann -- 5. Argentina: The Melancholy of Liberal Democracy / Aldo C. Vacz -- 6. Romania: The Anguish of Postcommunist Politics / Mary Ellen Fischer -- 7. Poland: A Troubled Transition / Sarah Meiklejohn Terry -- 8. Russia: Problems and Prospects for Democratization / Carol R. Saivetz -- Conclusion / Mary Ellen Fischer.
Includes index.
Keywords: Democracy -- Case studies